Peruvian efforts to contain COVID-19 fail to protect vulnerable population groups - Ian Vázquez-Rowe; Andrea Gandolfi (Elsevier, 2020)
Peru is arguably providing a robust governmental response in the initial stages of the COVID-19 outbreak, with early lockdown measures and the implementation of relatively ambitious economic safety nets to protect families and enterprises. Despite this initial optimism, structural deficiencies in the public health system, high informality in the labor market, the new wave of migrants from Venezuela and the extremely diverse cultural characteristics of many areas exacerbate the number of potentially highly vulnerable groups that may be left out of these safety nets unless additional efforts are enforced to improve social coverage. In this discussion we aim to identify some of these groups, highlighting the main challenges they face during the outbreak and proposing certain mitigation measures to balance the social policy response.